Bi2WO6 / AuNPs / Ni-MOF composite material, sensor and application
By combining Bi2WO6/AuNPs/Ni-MOF composite material with CRISPR/Cas12a system, an electrochemical/photoelectrochemical dual-mode sensor was constructed, which solved the problem of insufficient accuracy and sensitivity of OTA detection, and achieved high sensitivity and selectivity detection effects.
Patent Information
- Application Number
- CN202510681762.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-08-12
AI Technical Summary
In the prior art, the accuracy and sensitivity of OTA detection are insufficient, and single-mode sensors are susceptible to interference from high background signals or false positive/negative signals, affecting the detection accuracy.
Bi2WO6/AuNPs/Ni-MOF composite material is used as the sensing substrate, combined with the CRISPR/Cas12a system, an electrochemical/photoelectrochemical dual-mode sensor is constructed, and the conductivity of Z-type heterostructure and surface plasmon resonance effects of AuNPs are used to enhance electron migration and signal response.
The sensitivity and accuracy of OTA detection are improved, and the detection range of 1pg/mL to 100ng/mL is achieved. The detection limit is 0.04pg/mL in the photoelectric mode and 0.67pg/mL in the electrochemical mode, which has high selectivity and reproducibility and meets the on-site detection needs.
Smart Images

Figure CN120468248A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of food safety detection, and specifically to a Bi2WO6 / AuNPs / Ni-MOF composite material, a sensor and applications thereof. Background Art
[0002] Ochratoxin A (OTA) is a secondary toxic metabolite produced by toxic fungi such as Aspergillus and Penicillium. It is the most toxic and widespread ochratoxin. Due to its high chemical and thermal stability, OTA is difficult to degrade during storage and production. OTA is widely present in the growth, storage, and transportation of various foods and feeds, including but not limited to corn, oats, rice, coffee, spices, cocoa, wine, and beer. It is important to note that OTA is severely nephrotoxic, hepatotoxic, carcinogenic, teratogenic, and neurotoxic, posing a serious threat to human health. The International Agency for Research on Cancer has classified it as a Class IIB carcinogen. To ensure food safety and human health, a variety of methods are currently available for detecting OTA, such as chromatography and immunological methods. However, these methods often face challenges, such as expensive instrumentation, complex operation, long analysis times, and difficulty in antibody preparation. Therefore, there is an urgent need to develop a rapid, efficient, simple, and low-cost OTA detection method, particularly for on-site testing.
[0003] To address these challenges, biosensors have attracted widespread attention from analysts due to their advantages such as high sensitivity, simple operation, and fast analysis speed. Many biosensors have been developed, such as fluorescence sensors, colorimetric sensors, surface-enhanced Raman scattering sensors, photoelectrochemical (PEC) sensors, and electrochemical (EC) sensors. However, these sensors are often based on a single response mechanism and are easily affected by high background signals or false positive / negative signals, thus affecting their accuracy. Dual-mode sensors, due to their two independent signal transduction mechanisms and different response mechanisms, enable cross-verification of detection results, which can further improve the accuracy of detection results compared to single-mode sensors. Among the developed dual-mode sensing platforms, EC / PEC dual-mode detection has attracted widespread attention due to its advantages such as fast response, high sensitivity, good selectivity, portability, and low cost.
[0004] The prior art also provides some sensors for detecting OTA. For example, Chinese patent CN 108760852 B provides a photoelectrochemical aptamer sensor for detecting OTA, which uses a graphene / cadmium sulfide / molybdenum disulfide / nano-gold composite as a photoelectric active material and combines competitive reaction and steric hindrance effect to achieve dual amplification of photoelectric signals to prepare a sensor. 2+An electrochemical aptamer sensor based on an induced signal amplification strategy for the detection of ochratoxin A [J]. Analytical Laboratory, 2023, 42(5): 595-600.) proposed a Cu2+-induced signal amplification strategy. Using gold as a working electrode, a poly(T)-containing aptamer was bound to a DNA probe on the electrode surface by DNA hybridization, and copper nanoclusters were grown in situ to obtain an OTA aptamer sensor. However, the accuracy and sensitivity of sensors for detecting OTA provided by existing technologies, including the above-mentioned scheme, still need to be improved. Summary of the Invention
[0005] (1) Technical issues
[0006] The present invention aims to at least solve the problem of insufficient precision and accuracy of OTA detection in the prior art. The present application aims to provide a Bi2WO6 / AuNPs / Ni-MOF composite material for use as a sensing substrate modification, and combined with the trans-cleavage activity of CRISPR / Cas12a, to design a sensor with electrochemical / photoelectrochemical dual modes.
[0007] (2) Technical content
[0008] This solution provides a Bi2WO6 / AuNPs / Ni-MOF composite material, which is a structure in which gold nanoparticles Au NPs with a particle size of 13 to 17 nm are uniformly dispersed on the surface of a nickel-based metal-organic framework - bismuth tungstate Bi2WO6 / Ni-MOF (which broadens the visible light response range of Bi2WO6 and forms a Z-type heterostructure due to band structure matching);
[0009] The composite material is composed of Bi2WO6 / Ni-MOF and AuNPs at a ratio of (15-25) mg: (0.8-1.2)×10 -3 The obtained composite material is a sheet-like structure of different sizes.
[0010] Further preferred technical solution: the composite material is composed of Bi2WO6 / Ni-MOF and AuNPs at a ratio of 20mg:1.0×10 -3 mmol reaction ratio was prepared;
[0011] Among them: In this scheme, Bi2WO6 / Ni-MOF uses solid powder, and the source of AuNPs is chloroauric acid, which is prepared by adding the reducing agent sodium borohydride.
[0012] The Bi2WO6 / AuNPs / Ni-MOF composite material provided in this scheme has the following advantages over other sensing substrates: (1) The band structures of Bi2WO6 and Ni-MOF can be well matched, forming a Z-type heterostructure, which inhibits the recombination of photogenerated electrons and holes; (2) AuNPs, as one of the noble metal nanoparticles, has good conductivity and surface plasmon resonance effect, and can act as a solid electron mediator to increase light absorption and promote charge separation, thereby generating an enhanced (photo)current response; (3) Since Bi2WO6 / Ni-MOF and AuNPs can form a ternary solid-state Z-type heterojunction, the electron transfer rate between the electrode and the sensing substrate can be accelerated, thereby improving the (photo)electrochemical signal. Therefore, the novel (photo)electroactive material Bi2WO6 / AuNPs / Ni-MOF provided in this application can be used as a sensing substrate to significantly improve the sensitivity of the dual-mode sensor.
[0013] Further preferred technical solution: The preparation method of the composite material includes:
[0014] Bi2WO6 / Ni-MOF was dissolved in pure water, and tetrachloroauric acid was added and mixed, and then sodium borohydride was added as a reducing agent. After reacting for 20 to 40 minutes, AuNPs with a size of 13 to 17 nm were synthesized on the surface of Bi2WO6 / Ni-MOF. Finally, a solid product was obtained by centrifugation.
[0015] A further preferred technical solution: the Bi2WO6 / Ni-MOF is obtained by ultrasonically exfoliating Ni-MOF powder in a mixed solution of sodium tungstate, bismuth nitrate, hexadecyltrimethylammonium bromide and pure water, and then heating it at 500°C to 800°C for 20 to 28 hours by a solvent thermal method.
[0016] A further preferred technical solution: the Ni-MOF is obtained by adding nickel nitrate, terephthalic acid, and polyvinyl pyrrolidone to a mixed solution of N,N-dimethylformamide, pure water, and ethanol, and heating at 100°C to 200°C for 8 to 12 hours by a solvent thermal method.
[0017] This solution also provides a reaction solution, which consists of an "aptamer-activator" double-stranded structure and a CRISPR / Cas12a system.
[0018] Further preferred technical solution: the double-chain structure of the "aptamer-activator" is composed of the aptamer and the activator at a ratio of (1.0-1.5)×10 -6 μmol:(0.8~1.2)×10 -6 The mixture is mixed with 20 μmol of the mixture, heated at 90° C. to 100° C. for 3 to 7 mins, and then cooled to room temperature at a rate of 3° C. / s to 7° C. / s.
[0019] A further preferred technical solution: the CRISPR / Cas12a system consists of crRNA and Cas12a protein.
[0020] The reaction solution provided in this scheme can be used for the specific and sensitive recognition of OTA, amplifying the response signal, and trans-cleaving the ssDNA on the electrode surface, causing a change in the distance between the electroactive molecule Fc and the sensing interface, thereby causing a significant change in the electrochemical / photoelectrochemical signal, thereby realizing the electrochemical and photoelectrochemical dual-mode detection of OTA.
[0021] This scheme also provides the application of Bi2WO6 / AuNPs / Ni-MOF composite materials and reaction solutions in the preparation of sensors for detecting ochratoxin A.
[0022] A further preferred technical solution: the sensor includes a sensor based on electrochemical and photoelectrochemical dual signal modes;
[0023] Specifically, the sensor includes:
[0024] A reaction solution, a substrate, and a working electrode layer attached to the substrate;
[0025] The reaction solution comprises the aptamer-activator double chain and the CRISPR / Cas12a system according to any one of claims 1 to 4;
[0026] The surface of the working electrode layer is sequentially coated with the Bi2WO6 / AuNPs / Ni-MOF composite material according to any one of claims 1 to 4, ssDNA-Fc and 6-mercaptohexanol (MCH).
[0027] A further preferred technical solution: the nucleotide sequence of the aptamer is: 5'-GAT CGG GTG TGG GTGGCG TAA AGG GAG CAT CGG ACA-3'; and / or,
[0028] The nucleotide sequence of the activator is: 5'-CTC CAT AGT GTC CGA TGC TC-3'; and / or,
[0029] The nucleotide sequence of the crRNA is: 5'-UAA UUU CUA CUA AGU GUA GAU GAG CAU CGGACA CUA UGG AG-3'; and / or,
[0030] The nucleotide sequence of the ssDNA-Fc is: 5'-SH-TCA GTG TGG AAA ATC TCT AGC AGT CAGTGT-ferrocene-3'.
[0031] A further preferred technical solution: the working electrode layer is based on an indium zinc oxide glass electrode, and the Bi2WO6 / AuNPs / Ni-MOF composite material, ssDNA-Fc and MCH are sequentially coated on the surface of the indium zinc oxide glass electrode.
[0032] This solution also provides a method for quantitatively detecting ochratoxin A, which comprises the steps of detecting using the sensor, specifically comprising:
[0033] After incubating the test sample with the aptamer-activator double-stranded structure for 30 to 50 minutes, a reaction solution is obtained; the reaction solution is mixed with the Cas12a-crRNA complex and reacted at 37°C for 20 to 40 minutes to obtain a test solution; then, the test solution is dropped onto the surface of the working electrode layer and reacted at 37°C for 30 to 50 minutes; finally, electrochemical and photoelectrochemical signal detection are performed by differential pulse voltammetry and time-current curve, respectively, and a fitting curve of electrochemical signal / photocurrent intensity and ochratoxin A concentration is drawn to achieve quantitative detection of ochratoxin A.
[0034] A further preferred technical solution: the detection range of the sensor in the electrochemical mode is 1 pg / mL to 100 ng / mL, and the detection range in the photoelectric mode is 0.1 pg / mL to 100 ng / mL.
[0035] The electrochemical / photoelectrochemical dual-mode sensor provided in this application has the following mechanism for detecting OTA: Figure 1 As shown, the details are as follows:
[0036] Initially, ssDNA-Fc is immobilized on the surface of a working electrode modified with Bi2WO6 / AuNPs / Ni-MOF via Au-S bonds. The reaction solution contains an aptamer-activator duplex and the CRISPR / Cas12a system. In the absence of OTA, the activator in the test solution is locked and unable to bind crRNA, resulting in inhibition of the trans-cleavage activity of CRISPR / Cas12a and no cleavage of the ssDNA-Fc. Because the Fc molecule has an inhibitory effect on the photoelectric signal, the sensor produces a weak photocurrent response in the photoelectric mode; in the electrochemical mode, the sensor generates a strong Fc oxidation peak current. In the presence of OTA, the specific binding of the target to the aptamer opens the aptamer-activator duplex, causing the activator to trigger the trans-cleavage activity of CRISPR / Cas12a, random cleavage of the ssDNA-Fc, and detachment of the Fc molecule at the electrode interface. At this point, the sensor's photocurrent response increases, while the Fc oxidation peak current decreases. Therefore, the dual-mode sensor can realize electrochemical / photoelectrochemical dual signal detection of OTA based on the relationship between the oxidation peak current change / photocurrent signal change of Fc and the OTA concentration, thereby providing self-verification for the analysis results and improving the reliability of detection.
[0037] The Bi2WO6 / AuNPs / Ni-MOF composite material prepared in this application can show good electrochemical activity and photoelectrochemical performance, and can be used as a sensing substrate for electrochemical / photoelectrochemical activity, which is beneficial to improve detection sensitivity. When the analyte OTA is present, CRISPR / Cas12a randomly cuts ssDNA-Fc, causing simultaneous changes in the electrochemical / photoelectrochemical signals. Based on the number of Fc molecules detached, quantitative detection of OTA is achieved by comparing the relationship between the changes in electrochemical / photoelectrochemical signals and the concentration of the target.
[0038] Furthermore, the present application makes a dual-mode sensor with the Bi2WO6 / AuNPs / Ni-MOF composite material and the reaction liquid. On the one hand, compared with the single-mode analysis method, the dual-mode sensor has independent signal conversion and output modes, and the detection results can be mutually verified to avoid false alarms of false signals. On the other hand, the CRISPR / Cas12a-driven Bi2WO6 / AuNPs / Ni-MOF dual-mode sensor for detecting OTA constructed in the present application has a detection range of 1pg / mL to 100ng / mL in the electrochemical mode and a detection range of 0.1pg / mL to 100ng / mL in the photoelectric mode, showing a low detection limit and has good application prospects in food safety testing.
[0039] (3) Technical effects
[0040] The above structure enables this solution to have the following beneficial effects:
[0041] 1. This application uses Ni-MOF as a carrier and prepares Bi2WO6 / AuNPs / Ni-MOF composite materials through in situ synthesis and in situ reduction methods to modify the sensing interface, improve the electron transfer rate and photoelectric signal conversion efficiency of the electrode surface, and enhance the electrochemical / photoelectrochemical signal response;
[0042] 2. In this application, the specific recognition of ochratoxin A and the aptamer can activate the trans-cleavage activity of CRISPR / Cas12a in the reaction solution, causing a change in the distance between the electroactive molecule Fc and the sensor interface, thereby causing a significant change in the electrochemical / photoelectrochemical signal;
[0043] 3. The dual-mode aptamer sensor constructed in this application has the advantages of low cost, simple operation, and miniaturization, meeting the needs of on-site detection;
[0044] 4. This application successfully constructed a dual-mode OTA sensor based on a Bi2WO6 / AuNPs / Ni-MOF heterostructure sensing strategy that combines CRISPR / Cas12a. The detection range in electrochemical mode can be used to detect OTA in the range of 1pg / mL to 100ng / mL, with a detection value of 0.67pg / mL. The detection range in photoelectrochemical mode can be used to detect OTA in the range of 0.1pg / mL to 100ng / mL, with a detection value of 0.04pg / mL. Since the results obtained in different detection modes can be mutually verified, the reliability of sensor detection can be improved. In addition, the sensor also exhibits high selectivity and reproducibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0046] Figure 1 Schematic diagram of the principle of OTA detection by the electrochemical / photoelectrochemical dual-mode aptamer sensor provided in this application;
[0047] Figure 2 TEM images of the Bi2WO6 / AuNPs / Ni-MOF composite material prepared in Example 1, wherein A is a TEM image of Bi2WO6, B is a TEM image of the Bi2WO6 / Ni-MOF composite material, and C is a TEM image of the Bi2WO6 / AuNPs / Ni-MOF composite material;
[0048] Figure 3UV-visible diffuse reflectance absorption spectra of different materials, where a is Ni-MOF, b is Bi2WO6, c is Bi2WO6 / Ni-MOF, and d is Bi2WO6 / AuNPs / Ni-MOF;
[0049] Figure 4 Photoelectric response curves of different materials, where a is bare ITO electrode, b is Ni-MOF, c is Bi2WO6, d is Bi2WO6 / Ni-MOF, and e is Bi2WO6 / AuNPs / Ni-MOF;
[0050] Figure 5 The AC impedance spectra of the sensor modified layer by layer, where a is a bare ITO electrode, b is Bi2WO6 / AuNPs / Ni-MOF / ITO, c is ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO, d is MCH / ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO, and e is activated CRISPR / Cas12a / MCH / ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO;
[0051] Figure 6 The photoelectric response curves of the sensor modified layer by layer, where a is a bare ITO electrode, b is Bi2WO6 / AuNPs / Ni-MOF / ITO, c is ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO, d is MCH / ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO, and e is activated CRISPR / Cas12a / MCH / ssDNA-Fc / Bi2WO6 / AuNPs / Ni-MOF / ITO;
[0052] Figure 7 The time-current curves of the sensor corresponding to different concentrations of OTA;
[0053] Figure 8 The linear fitting curves of the logarithmic value and photocurrent of different OTA concentrations are shown;
[0054] Figure 9 The differential pulse voltammetry curves of the sensor corresponding to different concentrations of OTA;
[0055] Figure 10 The linear fitting curves of the logarithmic values of OTA at different concentrations and the Fc oxidation peak current are shown;
[0056] Figure 11 Selectivity test results of the dual-mode sensor provided for this application;
[0057] Figure 12The reproducibility test results of the dual-mode sensor provided in this application. DETAILED DESCRIPTION
[0058] The following will provide a clear and complete description of the technical solutions in the embodiments of the present invention, in conjunction with the accompanying drawings. Obviously, the described embodiments are only a portion of the embodiments of the present invention, not all of them; all other embodiments derived by persons of ordinary skill in the art based on the embodiments of the present invention without inventive effort are also within the scope of protection of the present invention.
[0059] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0060] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0061] Example 1
[0062] This embodiment provides a Bi2WO6 / AuNPs / Ni-MOF composite material, the preparation method of which includes the following steps:
[0063] (1) Preparation of 2D Ni-MOF sheets
[0064] First, 20 mL of N,N-dimethylformamide, 20 mL of ultrapure water, and 20 mL of ethanol were added to a beaker and stirred for 10 minutes until a transparent solution was formed. Second, 0.880 g of nickel nitrate, 0.240 g of terephthalic acid, and 1.20 g of polyvinylpyrrolidone (K30) were added to the above solution in sequence. After magnetic stirring for 1 hour, the reaction mixture was transferred to a 100 mL polytetrafluoroethylene-lined autoclave, heated at 150°C for 10 hours, and cooled to ambient temperature. The solid product was collected by centrifugation and washed alternately with ultrapure water and ethanol three times. Finally, the dark green product was dried in a vacuum drying oven at 60°C for 12 hours to obtain 2DNi-MOF sheets.
[0065] (2) Preparation of Bi2WO6 / Ni-MOF
[0066] First, 0.1649 g of sodium tungstate, 0.4851 g of bismuth nitrate, and 0.025 g of hexadecyltrimethylammonium bromide were dispersed in 40 mL of ultrapure water and stirred continuously for 30 min to obtain a homogeneous solution A. 0.145 g of Ni-MOF was dispersed in 20 mL of ultrapure water to form a suspension B. Subsequently, the suspension B was added dropwise to the homogeneous solution A under magnetic stirring at ambient temperature. After stirring for 1 h, the mixed solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave, heated at 120 °C for 24 h, and cooled to ambient temperature. Finally, the solid product was collected by centrifugation and washed alternately with ultrapure water and ethanol three times. The light green product was placed in a vacuum drying oven at 60 °C for 10 h to obtain Bi2WO6 / Ni-MOF powder.
[0067] (3) Preparation of Bi2WO6 / AuNPs / Ni-MOF
[0068] First, 20 mg Bi2WO6 / Ni-MOF was added to 10 mL ultrapure water and a homogeneous solution was obtained by ultrasonic treatment. Then, 100 μL of 10 mM chloroauric acid solution (i.e., 1×10 -3 mmol) and stirred for 10 min; then, 20 μL of freshly prepared sodium borohydride solution with a molar concentration of 0.1 M was added for reduction, and the reaction was continued for 30 min; finally, the solid product was collected by centrifugation and washed alternately with ultrapure water and ethanol three times; the gray product was placed in a vacuum drying oven at 60 ° C for 10 h to obtain Bi2WO6 / AuNPs / Ni-MOF powder.
[0069] The three different materials prepared by the above method were observed by transmission electron microscopy. The results are as follows: Figure 2 As shown;
[0070] Depend on Figure 2 It can be seen that Bi2WO6 shows a 3D nanoflower morphology (such as Figure 2 Bi2WO6 nanoflowers are evenly covered on the surface of Ni-MOF, forming a closely contacted heterostructure (as shown in Figure 1). Figure 2 As shown in B); AuNPs with a size of 13 to 17 nm are dispersed on the surface of Bi2WO6 / Ni-MOF (as shown in Figure 2 (as shown in C).
[0071] Furthermore, the light absorption properties of the material were investigated by UV-visible diffuse reflectance absorption spectroscopy, and the results were as follows: Figure 3 As shown;
[0072] Depend on Figure 3It can be seen that the original Ni-MOF exhibits obvious visible light absorption, and its absorption edge can reach about 579nm (curve a); the absorption edge of Bi2WO6 appears at about 443nm, which can be attributed to its inherent band gap absorption (curve b); compared with the original Ni-MOF, the absorption of Bi2WO6 / Ni-MOF composite material shifts to longer wavelengths, improving the utilization of visible light (curve c); and after in situ synthesis of AuNPs, the absorption of the composite material to ultraviolet to visible light is significantly enhanced, indicating that the introduction of AuNPs greatly improves the light utilization efficiency (curve d); the absorption edges of Bi2WO6 / Ni-MOF (curve c) and Bi2WO6 / AuNPs / Ni-MOF (curve d) composite materials are 521nm and 743nm, respectively, which are longer than the original Ni-MOF, indicating that it can capture and utilize higher absorption edges to produce more e - / h + Therefore, Bi2WO6 / AuNPs / Ni-MOF can effectively inhibit the photogenerated - / h + The recombination of the pairs leads to the enhancement of the photocurrent;
[0073] Subsequently, the performance of Bi2WO6 / AuNPs / Ni-MOF was tested by time-current curve and compared with Ni-MOF, Bi2WO6 and Bi2WO6 / Ni-MOF materials. Figure 4 As shown;
[0074] Depend on Figure 4 It can be seen that Ni-MOF and Bi2WO6 exhibit smaller photocurrents due to their weak light absorption and serious recombination of photogenerated carriers. In comparison, the Bi2WO6 / Ni-MOF composite material exhibits a more obvious photocurrent signal, which is due to the effective separation of photogenerated electron-hole pairs due to the matching of energy bands.
[0075] It is worth noting that the photocurrent signal of the Bi2WO6 / AuNPs / Ni-MOF composite material prepared in Example 1 is the largest, which is attributed to the establishment of a Z-type heterojunction with AuNPs as a solid-state electron mediator. The photogenerated electrons can quickly migrate from the conduction band of Bi2WO6 to the valence band of Ni-MOF, resulting in a significant enhancement of the photoelectric signal.
[0076] Example 2
[0077] This example provides a 20 mg:1.0×10 -3 The electrochemical / photoelectrochemical dual-mode sensor of Bi2WO6 / AuNPs / Ni-MOF composite material was prepared with a reaction ratio of mmol. The preparation method of the sensor is as follows:
[0078] Step a: Preparation of dual-mode sensor
[0079] (a-1) The indium zinc oxide glass electrode was washed with acetone, ethanol, and ultrapure water for 10 min, respectively, and then dried under nitrogen flow;
[0080] (a-2) 10 μL of a 2.00 mg / mL ultrapure aqueous solution of the prepared Bi2WO6 / AuNPs / Ni-MOF composite material was drop-coated on the surface of the bare indium zinc oxide electrode prepared in step a, dried at room temperature, and the electrode surface was rinsed with ultrapure water and dried;
[0081] (a-3) 10 μL of 1.0 μg / mL ssDNA-Fc was added dropwise onto the surface of the Bi2WO6 / AuNPs / Ni-MOF modified working electrode layer;
[0082] (a-4) 3 μL of MCH solution was added dropwise to the surface of the working electrode layer to block the nonspecific active sites on the electrode surface.
[0083] (a-5) Drying to obtain an electrochemical / photoelectrochemical dual-mode sensor for detecting OTA.
[0084] Step b, preparing the test solution:
[0085] (b-1) 10 μL of aptamer (1.25 μM) and 10 μL of activator (1.0 μM) were mixed and heated at 95°C for 5 min. The mixture was then immediately cooled to 25°C at a rate of 5°C / s to obtain a double-stranded "aptamer-activator" structure.
[0086] (b-2) Mix 10 μL of OTA solution with 10 μL of aptamer-activator solution and incubate for 40 min to obtain a reaction solution;
[0087] (b-3) The reaction solution was mixed with 2 μL of 10× Buffer, 1 μL of crRNA, 1 μL of Cas12a protein, and 15 μL of ultrapure water, and reacted at 37°C for 30 min to obtain a test solution;
[0088] (b-4) Add 10 μL of the test solution to the sensor surface obtained in step a, and react at 37° C. for 60 min. After the reaction is complete, detect the electrochemical and photoelectrochemical signals of the sensor to obtain the test results.
[0089] The detection effect of the electrochemical / photoelectrochemical dual-mode sensor prepared by the above method on OTA was tested as follows:
[0090] First, 10 μL of OTA solutions with different concentrations of 0.1 pg / mL to 100 ng / mL were incubated with 10 μL of the "aptamer-activator" double-stranded structure for 40 minutes, mixed with the Cas12a-crRNA complex, and reacted at 37°C for 30 minutes; then, 10 μL of the reaction solution was added dropwise to the electrode surface and reacted at 37°C for 40 minutes; in each modification step, the electrode surface was rinsed with PBS to remove unbound molecules; finally, detection was performed in electrochemical detection mode and photoelectric detection mode, respectively, and the results are shown in Figure 2. Figures 7 to 10 As shown;
[0091] In the photoelectric detection mode, the photoelectrochemical signal is detected by the time-current curve. The response curve is as follows: Figure 7 As shown in the figure, the fitting curve of photocurrent intensity and OTA concentration logarithm is drawn as follows Figure 8 shown by Figure 7 and Figure 8 It can be seen that the sensor provided in this application has a detection range of 0.1 pg / mL to 100 ng / mL in the photoelectric detection mode, and its linear equation is I = 0.42 lgc OTA +2.57(R 2 =0.994), with a detection limit of 0.04 pg / mL;
[0092] In the electrochemical detection mode, detection was performed by differential pulse voltammetry, and the response curve was as follows: Figure 9 As shown, the logarithmic fitting curve of the peak current of Fc oxidation and OTA concentration is drawn as shown in Figure 10 shown by Figure 9 and Figure 10 It can be seen that the sensor provided in this application has a detection range of 1 pg / mL to 100 ng / mL in the electrochemical detection mode, and its linear equation is I Fc =-0.10lgc OTA +1.15(R 2 =0.996), with a detection limit of 0.67 pg / mL;
[0093] Interfering fungal toxins that may exist in actual samples, such as zearalenone (ZEN), deoxynivalenol (DON) and aflatoxin B1 (AFB1), were used to test the selectivity of the dual-mode sensor. The results are shown in Figure 2. Figure 11 As shown;
[0094] Depend on Figure 11 The results show that the signal response of the interfering fungal toxin sample is consistent with that of the blank sample; when the target compound OTA is present in the sample, the sensor shows a significant signal change, indicating that the sensor has good selectivity;
[0095] In addition, the reproducibility of the dual-mode sensor was tested, and the results were as follows: Figure 12 As shown;
[0096] Depend on Figure 12 The results show that the relative standard deviations of the electrochemical signal and the photoelectrochemical signal responses are 3.48% and 3.24%, respectively, indicating that the dual-mode sensor has good reproducibility.
[0097] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A Bi2WO6 / AuNPs / Ni-MOF composite material, characterized in that: The composite material is Bi2WO6 nanoflowers uniformly covering the surface of Ni-MOF to form a Z-type heterostructure to obtain Bi2WO6 / Ni-MOF, and AuNPs with a size of 13 to 17 nm are dispersed on the surface of Bi2WO6 / Ni-MOF; The composite material is composed of Bi2WO6 / Ni-MOF and AuNPs in a ratio of 15mg to 25mg: 0.8×10 -3 mmol~1.2×10 -3 The composite material was prepared with a reaction ratio of mmol, and the obtained composite material was a sheet structure of different sizes.
2. A Bi2WO6 / AuNPs / Ni-MOF composite material according to claim 1, characterized in that The preparation method of the composite material comprises: Bi2WO6 / Ni-MOF was dissolved in pure water, tetrachloroauric acid was added and mixed, and then the reducing agent sodium borohydride was added and reacted for 20 to 40 minutes to synthesize AuNPs with a size of 13 to 17 nm on the surface of Bi2WO6 / Ni-MOF. Finally, the solid product was obtained by centrifugation.
3. The Bi2WO6 / AuNPs / Ni-MOF composite material according to claim 2, characterized in that: The Bi2WO6 / Ni-MOF is obtained by heating Ni-MOF powder in a mixed solution of sodium tungstate, bismuth nitrate, hexadecyltrimethylammonium bromide and pure water at a temperature of 500°C to 800°C for 20 to 28 hours by a solvent thermal method.
4. The Bi2WO6 / AuNPs / Ni-MOF composite material according to claim 3, characterized in that The Ni-MOF is prepared by adding nickel nitrate, terephthalic acid and polyvinyl pyrrolidone into a mixed solution of N,N-dimethylformamide, pure water and ethanol, and heating the mixture at 100° C. to 200° C. for 8 to 12 hours by a solvothermal method.
5. A reaction solution, characterized in that The reaction solution consists of a double-stranded "aptamer-activator" structure and a CRISPR / Cas12a system, which is used to sensitively identify ochratoxin A, thereby trans-cutting the single-stranded DNA modified with ferrocene (ssDNA-Fc) on the electrode surface, causing a change in the distance between the electroactive molecule ferrocene and the sensing interface, and then causing a significant change in the electrochemical / photoelectrochemical signal, thereby achieving electrochemical and photoelectrochemical dual-mode detection of ochratoxin A.
6. A reaction solution according to claim 5, characterized in that: The "aptamer-activator" double-chain structure consists of an aptamer and an activator at a density of 1.0×10 -6 μmol~1.5×10 -6 μmol:0.8×10 -6 μmol~1.2×10 -6 The mixture is mixed with 20 μmol of the mixture, heated at 90° C. to 100° C. for 3 to 7 mins, and then cooled to room temperature at a rate of 3° C. / s to 7° C. / s.
7. A reaction solution according to claim 5, characterized in that: The CRISPR / Cas12a system consists of crRNA and Cas12a protein.
8. Use of a Bi2WO6 / AuNPs / Ni-MOF composite material according to any one of claims 1-4 and a reaction solution according to any one of claims 5-7 in preparing a sensor for detecting ochratoxin A.
9. The use according to claim 8, characterized in that The sensor includes a sensor based on electrochemical and photoelectrochemical dual signal modes; The sensor comprises: A reaction solution, a substrate, and a working electrode layer attached to the substrate; The surface of the working electrode layer is sequentially coated with the Bi2WO6 / AuNPs / Ni-MOF composite material according to any one of claims 1 to 4, ssDNA-Fc and 6-mercaptohexanol; The reaction solution comprises the aptamer-activator double chain and the CRISPR / Cas12a system according to any one of claims 5 to 7; The nucleotide sequence of the aptamer is: 5'-GAT CGG GTG TGG GTG GCG TAA AGG GAG CAT CGGACA-3'; and / or, The nucleotide sequence of the activator is: 5'-CTC CAT AGT GTC CGA TGC TC-3'; and / or, The nucleotide sequence of the crRNA is: 5'-UAA UUU CUA CUA AGU GUA GAU GAG CAU CGG ACACUA UGG AG-3'; and / or, The nucleotide sequence of the ssDNA-Fc is: 5'-SH-TCA GTG TGG AAA ATC TCT AGC AGT CAG TGT-ferrocene-3'.
10. A method for quantitatively detecting ochratoxin A, characterized in that: The method comprises the steps of performing detection using the sensor according to claim 9, specifically comprising: The sample to be tested was mixed with the reaction solution, reacted at 37°C for 30-50 minutes, and then dripped onto the surface of the working electrode layer. Electrochemical and photoelectrochemical signal detection were performed using differential pulse voltammetry and time-current curves, respectively. A fitting curve of the electrochemical signal / photocurrent intensity and ochratoxin A concentration was drawn to achieve quantitative detection of ochratoxin A. The detection range of the sensor in electrochemical mode is 1 pg / mL to 100 ng / mL, and the detection range in photoelectric mode is 0.1 pg / mL to 100 ng / mL.
Citation Information
Patent Citations
A photoelectrochemical method for detecting ochratoxin A based on dual signal amplification
CN108760852B
Cited By
Application of Ag / Al-Bi2WO6 composite SERS substrate in detection of 4-MBA in industrial wastewater
CN121917529A
Application of Ag / Al-Bi2WO6 composite SERS substrate in detection of 4-MBA in industrial wastewater
CN121917529B
Uric acid sensing material, electrode, preparation method and application
CN122468809A
A uric acid sensing material, electrode, preparation method and application
CN122468809B
